2016
DOI: 10.1108/mrr-09-2014-0211
|View full text |Cite
|
Sign up to set email alerts
|

Reframing the influence of national culture with theory-based multi-resolution simulation models

Abstract: Purpose For several decades, national culture has been described as having major influence over international business outcomes. Yet national culture has been framed often by vague terms and simplistic scales. The purpose of this paper is to explain why and how the influence of national culture should be reframed. Design/methodology/approach Review of literature concerned with causation in the behaviour of individuals and groups: anthropology, cognition, psychology, cross-cultural psychology, cultural psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…From the cultural perspective, the contribution CQ to interaction involvement and job performance of call center agents in the Philippines could possibly be explained by some cultural characteristics of the Filipino which facilitate them to be more effective when interacting with foreign clients. This argument is supported by Fox (2016)’s research which suggested that national cultures can have some influence on organizational behaviors and work performance of employees. It is also consistent with a study of Thanetsunthorn and Wuthisatian (2018) which found that national culture tended to influence attitudes and behaviors of employees toward some organizational policies and practices.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…From the cultural perspective, the contribution CQ to interaction involvement and job performance of call center agents in the Philippines could possibly be explained by some cultural characteristics of the Filipino which facilitate them to be more effective when interacting with foreign clients. This argument is supported by Fox (2016)’s research which suggested that national cultures can have some influence on organizational behaviors and work performance of employees. It is also consistent with a study of Thanetsunthorn and Wuthisatian (2018) which found that national culture tended to influence attitudes and behaviors of employees toward some organizational policies and practices.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, considering the influence of a national culture that can affect attitudes and behaviors of employees toward organizational policies and practices (Fox, 2016; Thanetsunthorn and Wuthisatian, 2018), it is particularly important for the management to understand some cultural characteristics of call center agents that might affect their cross-cultural competence development. Given the influence of American culture in the Philippines that already makes many Filipinos have prior background knowledge about Western cultures, CQ training may not have as much impact on the development of cross-cultural communication competence of Filipinos call center agents.…”
Section: Discussionmentioning
confidence: 99%